Nifedipine in acute myocardial infarction: an assessment of left ventricular function, infarct size, and infarct expansion. A double blind, randomised, placebo controlled trial. Issue 4 (April 1988) - Gottlieb, S O; Becker, L C; Weiss, J L; Shapiro, E P; Chandra, N C; Flaherty, J T; Gottlieb, S H; Ouyang, P; Mellits, E D; Townsend, S N
Abstract : The influence of nifedipine on left ventricular ejection fraction, infarct size, and infarct expansion was studied in a prospective, double blind, randomised, placebo controlled trial in 132 patients with low risk acute myocardial infarction of less than 12 hours duration, defined by an initial left ventricular ejection fraction greater than 35% and clinical Killip class of less than or equal to II. Sixty four patients were assigned to nifedipine 120 mg/day and 68 to placebo. Treatment was started on average (SEM) 8.0 (0.2) hours after onset of pain and continued for six weeks. Gated blood pool scans, thallium scans, and cross sectional echocardiograms were performed before treatment and at 10 days. There were no significant differences between the two groups in age, sex, cardiac risk factors, or use of other medications. Mean (SEM) global left ventricular ejection fraction was not different before treatment (nifedipine group 53 (2%), placebo group 55 (2%) and did not differ at 10 days (nifedipine group 54 (2%), placebo group 52 (2%). There were also no differences in regional wall motion or regional ejection fractions. Thallium defects quantified by computer analysis were similar in both groups before treatment (nifedipine 7.8 (0.7), placebo 7.9 (0.7)) and at 10 days (nifedipine 5.3 (0.7) placebo 5.3 (0.7)). In the subgroup of patients with transmural infarction who had good quality echocardiograms and serial studies (n = 30), there was no difference in mean (SEM) baseline infarct segment lengths between the two groups (nifedipine 70 (4) mm, placebo 65 (4) mm); however, the nifedipine group demonstrated no significant change in infarct segment length between the initial and 10 day studies ( + 0.6 (3) mm) while there was a significant increase in the infarct segment length in the placebo group (+ 7.8 (4) mm). The infarct segment length increased by >/= 1 cm in seven (47%) placebo patients but in only one (7%) nifedipine patient. The nifedipine group had a significant initial 10% decrease in mean arterial pressure whereas there was no change in the in the placebo group; this blood pressure difference persisted for 10 days. Thus although the early administration of nifedipine has no detectable effect on clinical outcome and infarction size, it may reduce early infarct expansion via an afterload reduction mechanism in patients with transmural infarction. These initial results must be interpreted with caution and need to be confirmed in a larger trial.